Reducing Waste by Implementing Lean Maintenance Approach through the 5S Program - Shuwandi Sumantri M; Imaduddin Murdifin; Muhammad Syafii, A. Basalamah; Aryati Arfah (IECON: International Economics and Business Conference, 2024)
The purpose of this study is to evaluate the implementation of the 5S program in enhancing maintenance effectiveness and reducing waste in the workplace, as well as analyzing its impact on productivity and operational quality. The research method used is a case study with a descriptive approach to identify and analyze activities that contribute to waste in the maintenance process. The analysis tools include Big Picture Mapping to map the current value stream and identify potential waste, as well as a work area audit to assess the initial status of the company’s work area. The sample for this study consists of companies that implement lean principles and have maintenance programs requiring continuous improvement. The results of the study show that the implementation of the 5S program, which includes Seiri, Seiton, Seiso, Seiketsu, and Shitsuke, can create a more organized and efficient work environment, improve work rhythm that is faster and more precise, and lead to increased productivity and stable quality, meeting customer expectations.